Impact of Nominee Agreement on Mining Business Entities Against the Welfare of the People - Sumarsih, Ida (International Journal of Social Service and Research, 2024)
This study delves into the regulation of foreign share ownership and the prohibition of nominee agreements in the establishment of mineral and coal mining entities in Indonesia, aiming to ensure legal certainty and promote the welfare of the people, as mandated by Article 33 paragraph (3) of the 1945 Constitution. Employing three legal theories—basic legal values (Gustav Radbruch), legal system theory (Lawrence Friedman), and the welfare state—the research method incorporates both normative juridical and empirical juridical approaches. The findings reveal that nominee agreements, though legally questionable under Article 1320 of the Civil Code, serve as a means for foreign investors to secure their interests in Indonesian mining ventures. An Environmental Analysis of Law (EAL) employing the Cost-Benefit Analysis (CBA) method indicates a positive impact on the welfare of communities in Morowali and Kutai Kartanegara regencies due to these agreements. Proposing an ius constituent approach, the study advocates for relaxed foreign ownership regulations, allowing up to 51% ownership during the initial establishment period, accompanied by a mandatory divestment to 49% after ten years of exploration. Such a policy shift obviates the need for nominee agreements, ensuring both investment security and legal clarity. Supervisory mechanisms are recommended to oversee divestment and reinvestment processes, ensuring equitable distribution of mining dividends and bolstering legal certainty in mining operations. These proposed regulatory adjustments are envisioned to foster equitable resource management, thereby advancing the welfare of the Indonesian populace, particularly in Morowali and Kutai Kartanegara regencies.